2017
DOI: 10.1016/j.kint.2016.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid signaling through its receptor initiates profibrotic epithelial cell fibroblast communication mediated by epithelial cell derived connective tissue growth factor

Abstract: The expansion of the fibroblast pool is a critical step in organ fibrosis, but the mechanisms driving expansion remain to be fully clarified. We previously showed that lysophosphatidic acid (LPA) signaling through its receptor LPA1 expressed on fibroblasts directly induces the recruitment of these cells. Here we tested whether LPA-LPA1 signaling drives fibroblast proliferation and activation during the development of renal fibrosis. LPA1-deficient (LPA1−/−) or -sufficient (LPA1+/+) mice were crossed to mice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 51 publications
2
47
1
Order By: Relevance
“…The lifespan of Mkl1/Mkl2 dKO mice was over 10 weeks, slightly longer than Srf KO mice. Previous studies showed an injury-promoting role of SRF/MKL in kidney disease [25][26][27][28] ; in contrast, data here support SRF and MKL1/MKL2 in the maintenance of normal podocyte structure and function.…”
Section: Significance Statementcontrasting
confidence: 57%
“…The lifespan of Mkl1/Mkl2 dKO mice was over 10 weeks, slightly longer than Srf KO mice. Previous studies showed an injury-promoting role of SRF/MKL in kidney disease [25][26][27][28] ; in contrast, data here support SRF and MKL1/MKL2 in the maintenance of normal podocyte structure and function.…”
Section: Significance Statementcontrasting
confidence: 57%
“…The pro-healing activity of LPA is attributed to a combined effect on fibroblast proliferation and migration and to chemotactic activity toward macrophages; these are key events in wound healing [19]. LPA-LPAR1 signaling directly drives connective tissue growth factor (CTGF) expression after injury and induces the proliferation of primary proximal tubular epithelial cells [22] and primary mesothelial cells [23]. In our study, we showed that the concentration of LPA in CSF was positively correlated with LF thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when the LPA 1 receptor was blocked, profibrotic cytokines (connective tissue growth factor and transforming growth factor-β) are significantly down-regulated [114]. In one study, it was confirmed that LPA-LPA 1 signaling directly induces connective tissue growth factor (CTGF) expression in primary proximal tubular epithelial cells via the myocardin-related transcription factor-serum response factor pathway [116]. It was worth noting that the glomerular LPA1 receptor does not participate in the role of TIF caused by UUO [114].…”
Section: Lpar and Renal Fibrosismentioning
confidence: 95%